Flood Prone Area Analysis in the Wonosari Sub Watershed, Bondowoso Regency, East Java - Dimas Hafiz Aditama; Donny Harisuseno; Andre Primantyo Hendrawan (Jurnal Penelitian Pendidikan IPA, 2025)
Bondowoso Regency is known as a region highly susceptible to flood disasters. Factors contributing to the increased flood risk include the hydrological and topographical conditions present in the study area. Therefore, it is essential to identify and map areas that are vulnerable to flooding. Flood vulnerability is influenced by several parameters, including rainfall, soil type, land use, slope gradient, surface runoff, and elevation. The data used in this study were obtained from UPT PSDA WS Sampean, covering the period from 2013 to 2023. These parameters were processed using a weighting and scoring method. The assignment of scores and weights was based on the influence of each parameter on flood vulnerability, with each parameter assigned an equal value ranging from 1 to 5. An overlay analysis was then performed to generate a flood vulnerability map. The resulting vulnerability levels were classified into five categories: very low, low, moderate, high, and very high. The results show that the majority of flood-prone areas fall within the "high" vulnerability category, covering approximately 250.18 km² or about 41% of the total area of the Wonosari Sub-watershed. This finding can be validated by historical events in 2023, during which several flash floods were recorded.